Malignant lung PEComa (clear cell tumor): rare case report and literature review - Campos, Marcos Adriano Garcia; Vasques, Lucas Fernandes; Medeiros, Rafael Goulart de; Monteiro Cutrim, Érico Murilo; Favarin, Ana Júlia; Silva, Sarah Rebecca Machado; Silva, Gyl Eanes Barros; Moraes, Marcelo Padovani de Toledo; Zanatta, Mariana Lopes; Queiróz, Diego Aparecido Rios (Frontiers in Oncology, 2023)
Clear cell tumors of the lung (CCTL), or “sugar tumors” of lung, are very uncommon lesions and are mostly benign perivascular epithelioid cell (PEC) tumors with no specific morphologic features. Fewer than 100 cases have been reported; the aggressive nature demonstrated in sporadic reports has rarely been described in the literature. Although the course is generally described as benign, eight reported cases showed malignant behavior. We report a case of a PEC with a malignant presentation in a young man, correlating the main characteristics of the tumor with other cases reported in the literature to better elucidate this rare presentation. We also performed a literature review of reports on benign and malignant CCTL cases, with a focus on clinical, imaging, and immunohistochemical differentiation. CCTLs are rare tumors that require histopathological and immunohistochemical confirmation; to date, criteria that can predict malignant evolution are lacking.